Studies on Gall Induction and Life History of Dixothrips onerosus (Ananthakrishnan) Inducing Galls In Terminalia chebula (Retzius) in North West Indian Shiwaliks - Chander, Jagdish (Indian Forester, 2018)
Studies on gall induction and life history of the (Dixothrips onerosus) were carried out in Kalka, Pinjore and Morni areas ofHaryana Shiwaliks and Jaman Ki Sher (District Sirmaur), Bhota (District Hamirpur) and Bilaspur district of Himachal Pradesh. Three generations were noticed inside the gall under North West Indian Shiwalik conditions. By the first week of November, the galls dried up and small cracks appeared at the base of the gall. The adults left the galls through these cracks to pass winter among the fallen leaves, though some of them passed winter in late formed galls as well. The adults resumed their activity in February when the tender leaves started appearing on the plant The gall induction by this pest on hararin Shiwaliks assumes greater significance in view of the importance of its fruit in modern allopathic and Indian system of medicines, insect and host plant interactions, harm done by the insect to the host plant on one hand and possible use of galls in medicinal health, functional food, and nutraceuticals applications. The life history of Dixothrips onerous has also been worked out for the first time in the area.